THE ANTECEDENTS OF PLACE ATTACHMENT IN SELFIE TOURISM - Marchsela Putri, Diva; Luki Adiati Pratomo (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2024)
The purpose of this study is to to examine the relationship between selfie tourism, memorable tourism experience, hedonic well-being and travelers’ place attachment. This research is a hypothesis testing research conducted in Indonesia. Data was obtained by distributing questionnaires to 200 respondents who have visited various destinations in Indonesia. Respondents are people aged nineteen years and over. Data were tested using Strucural Equation Modeling (SEM) and Statistical Package for the Social Science (SPSS). The results of this study found that there was a positive influence between Selfie Tourism, Memorable Tourism Experience, Hedonic Well-Being, and Place Attachment. Therefore, tourism destination management and the government are advised to design and implement targeted programs that focus on infrastructure development, including well-designed public spaces, aesthetic spaces, and cultural centers, as one of their strategic marketing.